Effect of intravenous iron on outcomes of acute kidney injury. Issue 4 (22nd January 2016) - Clark, Barbara A.; Osadchuk, Liliana; John, Jones; Culver, Thuyanh; Marcus, Richard
Abstract : BACKGROUND: Little is known about benefit versus risk in treating iron deficiency anemia with intravenous (IV) iron in patients with acute kidney injury (AKI). Concerns about adverse outcomes may dissuade use and could contribute to greater use of red blood cell (RBC) transfusion. STUDY DESIGN AND METHODS: We performed a retrospective case‐control study of patients with AKI who received IV iron (cases) compared to those with AKI without IV iron (controls). RESULTS: We identified 67 cases and 67 controls matched for age, stage of chronic kidney disease, and severity of anemia (hemoglobin [Hb], 7.7 ± 0.1 mg/dL vs. 7.5 ± 0.1 mg/dL; p = 0.47). Cases tended to be sicker with longer length of stay (27 + 4 days vs. 15 + 1.3 days; p = 0.003) and more intensive care unit days (13 + 2 days vs. 5 + 1 days; p = 0.003), more often with diagnosis of sepsis and greater number of antibiotics used (2.7 ± 0.3 vs. 1.8 ± 0.2; p = 0.02). Sepsis and AKI preceded use of IV iron. Despite greater illness severity, there was no difference in dialysis (38.8% vs. 34.3%; p = 0.59), mortality (24% vs. 21%; p = 0.679), or severity and/or recovery of AKI. Discharge Hb was similar (9.0 ± 0.1 mg/dL vs. 9.1 ± 0.1 mg/dL; p = 0.47). IV iron was used later in the stay and hence the cases also had more RBC transfusions. CONCLUSIONS: We were unable to find any adverse consequences of use of IV iron when used to treat anemia in patients with AKI in regard to recovery of AKI or mortality even in patients with a diagnosis of sepsis. Consideration of preemptive use of IV iron in AKI with severe anemia is warranted to determine if this would reduce RBC transfusion.